Republic of Macedonia Foreign Policy : Diplomacy in the Middle of the Balkans. - Marolov, Dejan (Cambridge Scholars Publishing, 2013)
""The Republic of Macedonia is a particularly interesting case-study for analysts of international relations. Its very existence has been contested by its neighbors; its internal balance is delicate. Potentially, the country could, however, become a model of stability in a traditionally conflictual region. Dejan Marolov presents an encompassing, in-depth analysis of the country's foreign policy since the break-up of Yugoslavia. He examines relations with neighboring countries, as well as Maced ...